Quasi-States and Autonomies of Northeast China as the Instrument of Ensuring Economic Stability of Japan (Based on the Materials of the American Mass Media the 1930s) - Dudin, Pavel N.; Husainov, Zufar F. (International Journal of Economics and Financial Issues, 2016)
In article based on the materials of the American mass media the author constructs the autonomy process of Northeast China during the period preceding the Japanese-Chinese war of 1937-1945. The Japanese policy main stages on the creation of the semi-autonomous territories, the reasons interfering this plan implementation in whole, which it should be noted major confrontation in the Japan Cabinet, when the moderate politicians group supporting peaceful resolution of contradictions was headed by the Minister of Foreign Affairs, and the militarists group - the minister of army and the command of Kwantung army supporting him, are established. Concluded that, first, Japan, being afraid of the negative international reaction, tried to solve the problem not military, but diplomatic and methods, and secondly, the Japanese policy on the continent was inconsistent and it was expressed in impossibility at an initial stage to achieve the status of the autonomy for five Chinese provinces and to declare the Autonomous Council of East Hebei, which under control territory covered only small part of one of the Chinese provinces. Creation of the Hopei-Chahar Political Council allowed both the Japanese, and the Chinese sides “to save face”, and the military campaign, which began in the summer of 1937, finished the transition process of the China northeast provinces under the Japan control through the creation of the quasi-state the Chinese Republic by the end of 1937. Invaders received in the order such tools as the circulation of the precious metals and drugs, finance, oil monopoly, customs points, etc., thereby having provided complete control over the region economy. Keywords: Northeast China, autonomy, quasi-state, economic policy of Japan, mass media JEL Classifications: F13, N15, N25, N45